Legal Analysis of Regional Legislative Council Supervision of Regional Government Regarding Overlapping Mining Business Permits in North Maluku Province - Radina Hamza Hairun; Sultan Alwan; Nam Rumkel (Syntax Corporation Indonesia, 2023)
This study aims to assess the authority of provincial governments related to mining business permits. Moreover, DPRD supervision of local governments related to overlapping of overlapping mining business permits in North Maluku Province. The research method used in this study is the type of research used in the research is normative legal research as a process to find the rule of law, legal principles, and legal doctrines to answer the legal issues faced. The scientific logic that in normative legal research is built on scientific discipline and the ways in which normative legal science works, legal science whose object is law itself. The results of this study show that the authority of provincial governments related to mining business permits is explicitly regulated in the provisions of Article 14 paragraph (1) Law Number 23 of 2014 concerning Regional Government which reads